Soluble CD14 Enhances the Response of Periodontal Ligament Stem Cells to Toll-Like Receptor 2 Agonists - Christian Behm; Alice Blufstein; Johannes Gahn; Nazanin Noroozkhan; Andreas Moritz; Xiaohui Rausch-Fan; Oleh Andrukhov (Hindawi Limited, 2019)
Human periodontal ligament stem cells (hPDLSCs) do not express membrane-bound CD14, and their responsiveness to bacterial lipopolysaccharide (LPS) is drastically enhanced by soluble CD14 (sCD14), which is due to the facilitation of the interaction between LPS and Toll-like receptor- (TLR-) 4. Several studies also show that sCD14 enhances the responsiveness of different immune cells to TLR-2, but such effect in hPDLSCs has not been studied so far. In the present study, we investigated for the first time the potential effect of sCD14 on the hPDLSC response to two different TLR-2 agonists, in vitro. Primary hPDLSCs were stimulated with synthetic lipopeptide Pam3CSK4 or lipoteichoic acid (LTA) in concentrations 1-1000 ng/ml in the presence/absence of sCD14 (250 ng/ml). Additionally, the effect of different sCD14 concentrations (2.5-250 ng/ml) on the TLR-2 response was determined in Pam3CSK4- or LTA-triggered hPDLSCs. The resulting expression of interleukin- (IL-) 6, chemokine C-X-C motif ligand 8 (CXCL8), and chemokine C-C motif ligand 2 (CCL2) was measured by qPCR and ELISA. The production of IL-6, CXCL8, and CCL2 was gradually increased by both TLR-2 agonists and was significantly enhanced by sCD14. The response of hPDLSCs to low and submaximal concentrations of TLR-2 agonists (1-100 ng/ml) was most effectively enhanced by sCD14. The effect of sCD14 on TLR-2 response in hPDLSCs was concentration-dependent and was already detectable at low sCD14 levels. Our data showed that exogenous sCD14 significantly enhanced the responsiveness of hPDLSCs to TLR-2 agonists and enabled the detection of their small amounts. This effect was already detectable at low sCD14 levels, which are comparable to those in saliva and gingival crevicular fluid. Changes in the local sCD14 level may be considered as a crucial factor influencing the susceptibility of hPDLSCs to different pathogens and thus may contribute to the progression of periodontitis.